First-principles calculation of electronic density of states and Seebeck coefficient in transition-metal-doped Si–Ge alloys. (January 2021) - Yamada, Ryo; Masago, Akira; Fukushima, Tetsuya; Shinya, Hikari; Nguyen, Tien Quang; Sato, Kazunori
Abstract: High Z T value and large Seebeck coefficient have been reported in the nanostructured Fe-doped Si–Ge alloys. In this work, the large Seebeck coefficient in Fe-doped Si–Ge systems was qualitatively reproduced from the computed electronic density of states, where a hybrid functional, HSE06, was used for an exchange-correlation functional, as well as a special quasi-random structure (SQS) for a disordered atomic configuration. Furthermore, by replacing Fe with other transition metals, such as Mn, Co, Ni, Cu, Zn, and Au, a dopant that produces a large Seebeck coefficient in Si–Ge alloy systems was explored. It was found that the Mn-doped system produces a large Seebeck coefficient comparable with the Fe-doped system. Highlights: Hybrid functional DFT is used to calculate Seebeck coefficient of SiGe alloys. The investigation is applied to transition metal (Mn, Co, Fe, Ni, Cu, Zn, Au) doping. Large Seebeck coefficient in Fe-doped SiGe systems was qualitatively reproduced. Impurity states at band-edges of Fe-doped SiGe boost the Seebeck coefficient. Large Seebeck coefficient is also found in Mn-doped SiGe due to these impurity states.